2004
DOI: 10.1897/03-246
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk assessment of six human pharmaceuticals: Are the current environmental risk assessment procedures sufficient for the protection of the aquatic environment?

Abstract: In this study, exposure and ecotoxicity data of six human pharmaceuticals (carbamazepine, clofibric acid, diclofenac, ofloxacin, propranolol, and sulfamethoxazole) were collected, including our own experimental data and literature data. From this data collection, the two-tiered European draft guideline on the environmental risk assessment of human pharmaceuticals was tested. Measured environmental concentrations in effluents from France and in effluents and surface waters from Germany were compared to the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(231 citation statements)
references
References 38 publications
7
215
0
9
Order By: Relevance
“…Concentrations of DOC and OTC were significantly correlated with density of aquaculture (r = 0.74, 0.76, respectively) for June 2010 sampling event. As Nd not detected a (Halling-Sorensen et al 2000) b (Lutzhoft et al 1999) c (Eguchi et al 2004) d (Ferrari et al 2004) shown in Fig. 3, the peak concentrations of DOC and OTC all appeared in East Tiaoxi, where the aquaculture was intensive.…”
Section: Correlation With Potential Sourcesmentioning
confidence: 83%
“…Concentrations of DOC and OTC were significantly correlated with density of aquaculture (r = 0.74, 0.76, respectively) for June 2010 sampling event. As Nd not detected a (Halling-Sorensen et al 2000) b (Lutzhoft et al 1999) c (Eguchi et al 2004) d (Ferrari et al 2004) shown in Fig. 3, the peak concentrations of DOC and OTC all appeared in East Tiaoxi, where the aquaculture was intensive.…”
Section: Correlation With Potential Sourcesmentioning
confidence: 83%
“…The non-standard test data evaluated in this study (presented in Table 2[ [14][15][16][17][18][19][20][21][22]) have been selected for the current analyses since they were either (1) used in risk assessments of active pharmaceutical ingredients within the Swedish environmental classification and information system for pharmaceuticals [[23]; available at http:// www.fass.se] or (2) used in a previous evaluation of this classification system [24]. These selection criteria resulted in a total of nine references that was then evaluated according to the four methods.…”
Section: Evaluation Of Existing Reliability Evaluation Methodsmentioning
confidence: 99%
“…Using the four methods lead to the same evaluation result for two studies only [14,15], both were summarized as studies with unacceptable quality/not reliable. The evaluation result differed by one quality data level, from unacceptable quality/not reliable to acceptable quality/reliable with restrictions, for five studies [16][17][18][19][20] and by two quality data levels, from unacceptable quality/not reliable to high quality/reliable without restrictions, for two studies [21,22] (Table 13).…”
Section: Summary Of the Reliability Evaluation Of The Non-standard Tementioning
confidence: 99%
“…However, limited toxicity information about the PPCPs increased uncertainty in this assessment. Moreover, it has been found that risk assessment based on individual chemicals is often greatly lower than assessments based on chemical mixture (Ferrari et al, 2004;Backhaus and Karlsson, 2014). Therefore, the presence of the PPCPs and the potential ecological risks posed to the groundwater and reservoirs could be a serious issue.…”
Section: Environmental Risksmentioning
confidence: 99%